Idolizing “My Love from the Star”: Idol attachment and fanaticism of luxury brands - Cheah, Isaac; Liang, J.; Phau, Ian (John Wiley & Sons, 2018)
This study examines the influence of idol attachment and consumer fanaticism on consumers’ attitude toward celebrity product placement of luxury fashion brands in Korean television dramas. A 2 × 2 research design was used to examine two different product categories (fashion apparel vs. fashion accessories) and two celebrities (Kim Soo Hyun vs. Jun Ji-Hyun). Respondents were screened and limited to those who were aware of the Korean television drama My Love from the Star. The findings show that the gender of celebrity and the category of product placement have differential impacts on viewers or fans’ attitudes and intention toward the product placement.